2013
DOI: 10.1152/jn.00553.2012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of rodent somatosensory barrel cortex are correlated with learning a novel conditioned stimulus

Abstract: Long JD 2nd, Carmena JM. Dynamic changes of rodent somatosensory barrel cortex are correlated with learning a novel conditioned stimulus. J Neurophysiol 109: 2585-2595, 2013. First published March 6, 2013 doi:10.1152/jn.00553.2012.-The rodent somatosensory barrel cortex (S1bf) has proved a valuable model for studying neural plasticity in vivo. It has been observed that sensory deprivation or conditioning reorganizes sensory-driven activity within S1bf. These observations suggest a role for S1bf in somatosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…5 ). Similar compound excitation-inhibition effects of electrical stimulation have been reported in cortical circuits 30 - 32 . If the stimulation-induced rebound BF excitation were to impact behavior, one would predict to see speeding of RTs, because BF stimulation designed to enhance BF bursting amplitude leads to faster RTs 24 .…”
Section: Discussionsupporting
confidence: 78%
“…5 ). Similar compound excitation-inhibition effects of electrical stimulation have been reported in cortical circuits 30 - 32 . If the stimulation-induced rebound BF excitation were to impact behavior, one would predict to see speeding of RTs, because BF stimulation designed to enhance BF bursting amplitude leads to faster RTs 24 .…”
Section: Discussionsupporting
confidence: 78%
“…Not surprisingly, neuronal firing patterns changed as the animal learned to use the BMI control (BMI-b) and stopped pressing the pedal (BMI-o) compared to Behavioral Control (BC) as has been observed by several others (Figure 2A ; Ganguly and Carmena, 2009 ; Ganguly et al, 2011 ; Long and Carmena, 2013 ). During BC, a majority of neurons (87.5%) were responsive post-cue onset, encoding the intention to press the pedal (Manohar et al, 2012 ) but the proportion of responsive neurons decreased across experimental conditions (BMI-b: 2,279 of 2,628, 86.2%; BMI-o: 1,966 of 2,331, 84.3%; chi-square proportions test: χ 2 = 20.38, p < 0.001).…”
Section: Resultssupporting
confidence: 60%
“…The enhanced discrimination of the response is likely due to learning the BMI task. In a recent study of somatosensory learning, Long and Carmena observed similar increases in response magnitude and decreased baseline activity in sensory barrel field neurons that were well correlated to increasing performance in novel cross-modal sensory task (Long and Carmena, 2013 ). The same phenomenon was also observed during BMI learning in a motor context in which monkeys were trained under a BMI but were switched between epochs of BMI and behavioral control within single experimental sessions (Ganguly and Carmena, 2009 ; Ganguly et al, 2011 ; Knudsen et al, 2014 ).…”
Section: Discussionmentioning
confidence: 78%
“…Natural sensorimotor learning involves plasticity within the basal ganglia and the sensory, motor, and prefrontal cortices—brain areas that are responsible for adapting to new sensory information and associating sensory inputs with motor commands ( 143 ). Learning in a motor BMI also involves plasticity in, at a minimum, the basal ganglia and motor cortex ( 144 ), while learning to detect electrical stimulation requires (at least) plasticity in sensory cortical areas ( 145 ). However, electrical stimulation drives cortical plasticity even in the absence of any behavioral relevance ( 146 , 147 ), so learning within the context of a BMI will consist of a balance between adapting to stimulation-evoked responses, assigning stimulation-evoked responses behavioral relevance, and associating stimulation-evoked responses with motor commands.…”
Section: Artificial Sensation For Neural Prosthesesmentioning
confidence: 99%
“…Neurons typically respond to electrical stimulation by a short burst of excitation followed by a longer-lasting inhibition ( 117 ). After behavioral training, neurons have both a larger active response and a longer inhibitory phase compared with baseline ( 145 ). These changes show clear adaptation to novel experience.…”
Section: Artificial Sensation For Neural Prosthesesmentioning
confidence: 99%